Analysis of Rural Women's Access to Financial Services and Corporate Social Responsibility in Nigeria's Niger Delta Region - Joseph Ikechukwu Uduji; Elda Nduka Okolo-Obasi (African Governance and Development Institute (AGDI), 2023)
The purpose of this paper is to critically examine the multinational oil companies (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on enhancing rural women's financial inclusion in the areas of access to credit, insurance, propensity of the women to save and widening of economic opportunities in the Niger Delta. A total of 800 rural women were sampled across the Niger Delta region of Nigeria. Results from the use of a combined propensity score matching and logit model indicate that GMoU model made significant impact on closing the gaps in financial services, thereby removing women's constraints on their efforts to enhancing their financial literacy. The result also confirms that, innovative delivery channels and social networks of the GMoUs have reduced some costs in the areas of access to credit, insurance, propensity to save and widening of economic opportunities to rural women in the oil host communities. However, a further look at the rural women's participation in the CSR activities using SCOTDI, shows that even though the involvement of the women is appreciable, yet it is insignificant when compared with their male counterpart.
Keywords: 330; Financial services; rural women; corporate social responsibility; multinational oil companies; Nigeria; sub-Saharan Africa